Comparative Study and Quantitative Analysis of Stachydrine in Alfalfa Mother Tincture Prepared from Different Homoeopathic Pharmaceutical Companies - Saxena, Chitrlekha; P, Gajendragadkar M. (International Journal of Membrane Science and Technology, 2023)
Background: Stachydrine has been identified as the major alkaloid in alfalfa and it is positively correlated with protein contents. More stachydrine was present in leaves than in the stems of plants. Alkaloid was ascertained by using Mayer’s reagent and Isatin reagent. Uv-vis spectrophotometer is an apparatus used to encounter specific absorbance such Alkaloids, Phenols, etc. in the given samples quartz cuvette is utilized for the sample scrutiny. Aim: To compare Stachydrine content in Alfalfa mother tincture prepared from different Homoeopathic Pharmaceutical Companies. Methods: 1ml of Alfalfa mother tincture from various homoeopathic pharmaceutical companies were amalgamated with 1ml of Mayer’s reagent in different test tubes as A,B,C,D,E,F,G,H. Stachydrine absorbance value was confiscated in Uv-vis spectrophotometer at 264nm. Results: Following Results had been ascertained after passing all the samples at 264nm in Uv-vis spectrophotometer. Sample A: ADEL Alfalfa mother tincture sample: 3.456 Sample B: BJAIN PHARMA Alfalfa mother tincture sample: 3.557 Sample C: LORD’S Alfalfa mother tincture sample: 3.668 Sample D: MEDISYNTH Alfalfa mother tincture sample: 3.763 Sample E: SBL Alfalfa mother tincture sample: 3.498 Sample F: Dr. RECKEWEG Alfalfa mother tincture sample: 3.335 Sample G: SIMILIA Alfalfa mother tincture sample: 3.615 Sample H: WILLMAR SCHWABE Alfalfa mother tincture sample: 3.526 Conclusion: Stachydrine absorbance was quantified by using Uv-vis spectrophotometer at264nm. The results gained from study had flaunted that sample D has highest amount of Stachydrine.